Sensory integration strategies on repeated postural stability and neuromuscular adaptation in individuals with low back pain - Sung, Paul; Lee, Dongchul (European spine journal, 2025)
Background Individuals with low back pain (LBP) often exhibit balance impairments resulting from altered neuromuscular control and sensory integration deficits. Purpose This study aimed to compare differences in sway excursion and neuromuscular responses in maintaining spatial orientation and equilibrium between adults with and without LBP under eyes-open and eyes-closed conditions. Methods Thirty-two adults with LBP and 40 control subjects performed three repeated trials of unilateral standing tasks on a force platform. Center of pressure (COP) displacement on anteroposterior (AP) and mediolateral (ML) directions, center of gravity (COG), and COP-COG displacement were analyzed to assess postural stability and neuromuscular responses. Results For COP sway excursion, significant group interactions were observed between visual condition and repetition (F (2, 136) = 4.03, p < 0.05). Neuromuscular responses, assessed by COP-COG displacement, demonstrated significant group interactions across visual condition (F (1, 68) = 7.19, p < 0.01), repetition (F (2, 136) = 4.26, p < 0.05), and the combined effect of visual condition and direction (F (1, 68) = 8.15, p < 0.01). In the LBP group, neuromuscular response increased significantly in both eyes-open (t = -1.84, p < 0.05) and eyes-closed (t = 2.16, p < 0.05) conditions during the third trial in the ML direction. Conclusion These findings suggest that individuals with LBP exhibit distinct sway excursions under eyes-open conditions, but do not when their eyes are closed. The control group relied more on vision to maintain balance than the LBP group, who appeared to struggle with balance regulation independent of visual cues. Highlights Low back pain (LBP) may hinder postural stability when visual feedback is reduced. The increased sway in the mediolateral direction in the LBP group could elevate imbalance risks. Repeated balance tasks led to pronounced neuromuscular adaptations in the LBP group.